INTEGRASI PRINSIP ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) ATAS PRAKTIK KEBERLANJUTAN DALAM PENGELOLAAN BISNIS REAL ESTATE - Sanjaya, I Kadek Yoga; Atmadja, Anantawikrama Tungga; Darmawan, Nyoman Ari Surya (KRISNA: Kumpulan Riset Akuntansi, 2025)
Sustainability practices have become a global issue, yet many companies remain vulnerable in implementing ESG (Environmental, Social, and Governance) sustainability in their business lines. This study aims to provide a deeper understanding of the issues and identify (1) the background behind PT PSS management’s choice of a sustainable concept in business management, (2) the implementation of sustainability practices in business management, and (3) the alignment of the implementation of sustainability practices in business management at PT PSS with ESG principles. The method used in this study is a qualitative approach with a case study of PT PSS, employing an interpretive paradigm. The results show that (1) the background for PT PSS management’s choice of a sustainability concept is based on the company’s internal awareness, the influence of stakeholders, regulatory compliance, and business strategies aimed at enhancing company value, (2) the sustainability practices implemented by PT PSS in business management, from planning to maintenance, have been integrated with environmental, social, and governance initiatives, and (3) PT PSS has met ESG criteria and is in accordance with the ten ESG standards issued by the Ministry of Finance of the Republic of Indonesia. The implications of this study reveal the positive impacts received by PT PSS, the environment, and the community through the application of sustainability practices, and it is hoped that companies in Indonesia will start to integrate ESG principles into their business operations.